Analisis Struktural Dan Nilai Pendidikan Karakter Dalam Novel Sangkakala Di Langit Andalusia Karya Hanum Salsabiela Rais Dan Rangga Almahendra - Anita, Anita; Nurhasanah, Een; Pratiwi, Wienike Dinar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe the form of structure and character education values ​​contained in the novel Sangkakala in Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra. This type of qualitative research, with a qualitative descriptive method. The data source used in this research is a novel entitled Sangkakala in Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra. The theory used in this research is the structuralism theory of Robert Stanton (2012). The data collection technique used in the study used literature study techniques, reading and note-taking techniques. The data analysis technique used is three steps, namely data reduction, data presentation, and conclusion. The results of this study indicate that there are structural forms in the novel, namely there are story facts (in which the plot, characters and characterizations, and setting), themes, story mediums (which contain the title, point of view, and style of language). In addition, the values ​​of character education were also found including: religious values, juju, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the motherland, respect for achievement, peace-loving, friendly, fond of reading , environmental care, social care, and responsibility.